Residual compressive strength of concrete after exposure to high temperatures: A review and probabilistic models. (February 2023) - Shahraki, Marzieh; Hua, Nan; Elhami-Khorasani, Negar; Tessari, Anthony; Garlock, Maria
Abstract: The mechanical properties of concrete degrade after exposure to high temperatures during a fire event. Proper assessment of damage, determination of the remaining capacity of the structure, and recommendations for repair actions require the quantification of the reduction in the compressive strength of concrete after fire. This paper collects and analyzes the existing data on residual compressive strength of normal strength concrete in the literature. The analyses aim to identify the influential attributes that could be used to reduce scatter in the data. Parameters related to aggregate type, concrete mix, and testing protocol are studied. Subsets of the dataset for concrete with siliceous and calcareous aggregates are created. Data for siliceous concrete is further categorized based on the retaining time of the maximum temperature during the test. The subsets are used to propose probabilistic models for the residual compressive strength of concrete with siliceous and calcareous aggregates. The models follow the Weibull distribution and are continuous functions that can be implemented in analytical and computational frameworks. The medians of the proposed model and data are close to the Eurocode reduction factors for the siliceous concrete but fall below the Eurocode reduction factors for concrete with calcareous aggregate.